The Impact Of Gadget Use on Elementary School Students' Learning Focus in Undaan District, Kudus Regency - Supriyanto, Supriyanto (Jurnal Pendidikan Islam, 2025)
The rapid advancement of digital technology has transformed education by integrating gadgets into elementary students' learning processes. However, concerns have arisen regarding their negative effects on students' focus. This study examines the relationship between gadget usage intensity and students' learning focus in Undaan District, Kudus Regency. A quantitative research approach was employed, utilizing surveys and Structural Equation Modeling (SEM) to analyze causal relationships.The results reveal a significant negative correlation between excessive gadget use and learning focus (r = -0.62, p < 0.05). However, academic-oriented gadget use enhances concentration, while entertainment-oriented usage diminishes it. Parental supervision moderates these effects. These findings highlight the importance of controlled gadget use and technology-integrated learning strategies. Future research should explore cross-cultural perspectives and the impact of educational policies on gadget use.